Pendampingan Pra Nikah Bagi Santri Di Pondok Pesantren Irsyaduth Tholabah Bojonegoro Sebagai Upaya Preventif Pecreraian - Burhanatut Dyana; Indah Listyorini; Khurul Anam (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2026)
Abstract: The marriage of Islamic boarding school students (santri) has great potential to become a role model and be considered a potential example in marriage by the community, because it is not only based on legal provisions, but also deeply rooted in religious values. As a concrete step, the community service team compiled a Marriage Preparation handbook that is relevant to santri, made in a practical manner and equipped with attractive pictures. The method used was Participatory Action Research (PAR). This community service activity was carried out at the Irsyaduth Tholabah Islamic Boarding School in Bojonegoro and was attended by 55 santri consisting of male and female santri aged 17-22 years. The results of the community service showed that 49% of participants fully understood the material in the Marriage Preparation handbook that had been disseminated, and 82% of participants stated that this activity was very useful and served as a guideline for them before getting married. Through this community service, it is hoped that divorce among students can be avoided. Keywords: islamic boarding school student (santri); marriage; handbook; divorce Abstrak: Pernikahan santri memiliki potensi besar untuk menjadi role model dan dianggap sebagai panutan potensial dalam pernikahan oleh masyarakat, karena tidak hanya berlandaskan pada ketentuan hukum, tetapi juga berakar kuat pada nilai-nilai agama. Sebagai langkah konkrit, tim pengabdian menyusun handbook Persiapan Nikah yang relevan bagi santri, dibuat secara praktis dan dilengkapi dengan gambar menarik. Metode yang digunakan yaitu participatory Action Research (PAR). Kegiatan pengabdian ini dilakukan di Pesantren Irsyaduth Tholabah Bojonegoro dan diikuti oleh 55 santri yang terdiri dari santri putra dan santri putri dengan rentang usia 17-22 tahun. Hasil pengabdian menunjukkan bahwa 49% peserta sangat paham dengan materi handbook Persiapan Nikah yang telah disosialisasikan dan 82% peserta menyatakan bahwa kegiatan ini sangat bermanfaat dan menjadi pedoman bagi mereka sebelum melangsungkan pernikahan. Melalui pengabdian ini, diharapkan perceraian di kalangan santri dapat terhindari. Kata kunci: santri; pernikahan; handbook; perceraian